MODERN MARKETING TRENDS AND PROSPECTS FOR THE DEVELOPMENT OF TOURISM ENTREPRENEURSHIP IN UKRAINE - KOVALCHUK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores modern marketing trends and the prospects for the development of tourism entrepreneurship in Ukraine under the influence of the COVID-19 pandemic, the ongoing Russian-Ukrainian war, and the forthcoming post-war recovery period. It has been substantiated that the war has fundamentally transformed the marketing environment by reshaping consumer behavior, travel motivations, and the overall geography of tourism flows. Ukrainian tourism enterprises were forced to adapt to crisis conditions by reorienting their activities toward domestic tourism, promoting safe local routes, developing short-term recreation formats, and engaging in volunteer and community-support initiatives. The study highlights that digital transformation has become a decisive factor in maintaining competitiveness, with special emphasis on the use of social media, content and influencer marketing, online booking platforms, and virtual communication tools. These instruments not only support brand awareness and customer loyalty but also help restore trust in Ukraine’s tourism image during times of uncertainty. A separate focus is given to the growing importance of corporate social responsibility, ethical marketing, and communications based on empathy, trust, and authenticity as vital components of sustainable tourism branding. The article also notes the emergence of new tourism niches—such as military-historical, memorial, cultural, and volunteer tourism—that contribute to preserving collective memory, strengthening civic identity, and shaping a patriotic narrative of modern Ukraine. The authors emphasize that successful post-war recovery of the tourism industry requires the development of integrated marketing strategies aimed at innovation, partnership, and resilience. It is concluded that strategic marketing management in tourism entrepreneurship should rely on flexibility, innovation, and value-oriented approaches that combine economic efficiency with social responsibility. Such an approach will ensure the sustainable development, global competitiveness, and long-term resilience of Ukrainian tourism in the post-war period, while positioning Ukraine as a modern, dynamic, and ethically responsible travel destination in the international arena.